MINAT BELAJAR SISWA SEKOLAH DASAR PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI LINGKUNGAN SEKITAR - Ahmad Tarmizi Hasibuan; Riska Tiara Putri; Selfia Melati (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Citizenship education is a compulsory subject for elementary school children, this subject has the aim of patriotism from an early age. Student interest in Civic Education learning is less attractive due to unattractive, creative, and innovative learning methods or methods. This study aims to increase the learning interest of elementary school students in the subject of civic education. The study used a qualitative descriptive method with interview techniques to selected students. This method is carried out by observing and interviewing the selected respondents in which the subjects in this study are the fifth grade students of Dasae School, totaling 20 students, consisting of 10 female students and 10 male students having their address at Jl Taduan, Pancing, North Sumatera. And the results of the study indicate that learning Citizenship Education is less attractive. The lack of interest in student learning in PKN learning is caused by unattractive and boring learning methods and strategies.